Pengaruh Renang Gaya Bebas Terhadap Kebugaran Remaja Usia 12-15 Tahun - Ramadyani, Melinda; , Umi Budi Rahayu, S.Fis., S.Pd., M.Kes (2016)
Background: The fitness is optimal physical ability in a person's life. Fitness is one component that is very important for people, especially adolescents, as adolescence is a period in which they are growing and growing and active in everyday activities. At the age of 12-15 years is the golden age period in which fitness is one component of which is being increased pesat.salah one exercise that can be used is the freestyle routine exercise to improve fitness. Objective: To identify the influence of the fitness freestyle adolescents aged 12-15 years. Methods: The study was observational with cross sectional approach. The study design that point time apporoach, that every subject of study only observed once. Fitness measurements done using Bleep Test with a distance of 20 meters to run back and forth to the rhythm of there. Data were analyzed using regression, normality test using the likelihood ratio test similar, the variance test using ANOVA test, hypothesis testing using test cross tabs. Results: There freestyle influence the fitness of adolescents aged 12-15 years after the performed statistical tests using test cross tab ratio was obtained p-value of 0.000. Conclusion: There is the influence of the fitness freestyle adolescents aged 12-15 years. Keywords: Freestyle Swimming, Fitness, Bleep Test, Teen Age 12-15 Years.